Clandestine Philosophy New Studies on Subversive Manuscripts in Early Modern Europe - Paganini, Gianni; Jacob, Margaret C.; Laursen, John Christian (University of Toronto Press, 2019)
Clandestine Philosophy examines the circulation and consequences of 'clandestine philosophical manuscripts', a genre that flourished in the eighteenth century and included forbidden works such as erotic texts, political pamphlets, satires of court life and of the nobility, forbidden religious texts, and books about alchemy and the occult. The editors have brought together leading experts on the history of European philosophy to explore the circulation of radical ideas during the eighteenth century and the social, political, and cultural impact they had on eighteenth-century society.